DAYA HASIL GALUR-GALUR F1 HIBRIDA MENTIMUN (Cucumis sativus L) DI BANDUNG, BLITAR, BOGOR, GARUT DAN SUBANG - Uum Sumpena; Azlina Heryati Bakrie (Universitas Lampung, 2010)
Test of productivity was held in West Java (Bandung, Bogor, Garut, Subang) and in East Java, Blitar (Pakunden sub district and Sukorejo sub district), at elevation 20— 400 sea level. The soil type are Aluvial Latosol and Sandy loam. The Experiment was conducted held 2009 from 2010 during dry season. Randomized Bloc Design was used for this experiment, with three replications and twelve entries. F1 hibrida lines were 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 and two F1 hibrid varieties: Hercules and Asian Star. The treatment was repeated three times as chek varieties, planting distance is 40 x 60 cm. This experiment purpose of is to choose the best hybrid line of cucumber for released variety. Statistics are analysis with Duncan multiple range test 5 % showed that the total yield of F1 hybrid 1 and the hybrid 7 is significantly higer than the F1 hybrid Hercules but not to the Asian Star production.Key words: yield, F1 hybrid, line, cucumber, location